Learning vocabulary with the support of sustained exposure to captioned video: do proficiency and aptitude make a difference?. Issue 4 (8th August 2019) - Suárez, Maria del Mar; Gesa, Ferran
ABSTRACT: Video viewing can be a valuable resource to expose students to large quantities of input so they can improve their vocabulary and content comprehension. Most studies so far have used short clips and have not explored in much detail the effects of individual differences (IDs) such as aptitude, listening skills and vocabulary size. This paper aims to address this gap by exposing 57 Grade-10 EFL learners and 60 university students to captioned video. On a weekly basis over an academic term, all learners were pre-taught a set of target words (TWs); half of them (the experimental group) were additionally shown captioned episodes from a TV series containing the TWs. All learners were pre- and post-tested on the TW forms and meanings. Results revealed significant differences between experimental and control groups in the learning of TWs in the high school population, but not among university participants. A main effect for proficiency was observed on the learning scores for both TW forms and meanings. However, language aptitude was only a significant factor for TW meanings. Results are discussed regarding how video viewing and these IDs mediate vocabulary learning.